Belle Epoque - Gernando Trueba (1993)
Spain 1931. As the days of the monarchy draw to a close, Fernando, a young, idealistic soldier deserts the army. Fate leads him to the home of a wise and witty old painter, Manolo. The two become great friends. But the day arrives when Fernando must leave to make room for the arrival of Manolo's four daughters. Rocio, a born flirt, Violeta, rebellious, strong and dangerous, Clara, the oldest, a widow, Luz, the youngest, spoiled and willful. Fernando finds a way to stay, much to the delight of Manolo's daughters. Luz, madly in love becomes increasingly jealous as her sisters each seduce Fernando. Sexual entanglements, joys and sorrows abound as Fernando finds a home in Manolo's family. He doesn't know it, but these will always be the best days of his life.